Comprehensive analysis of real-world data on liraglutide treatment in patients with obesity: a multicenter national study - Hepsen, Sema; Haymana, Cem; Cavnar Helvaci, Burcak; Durantas, Halil; Toros, Bora; Cakmak, Ramazan; Sonmez, Alper (Bmc, 2025)
Background : The study aimed to evaluate real-world data on liraglutide by assessing its efficacy, associated side effects, adverse events, and impact on metabolic parameters within the context of a multicenter national study. Methods : This retrospective observational study analyzed data from 1009 patients across 38 endocrinology units from T & uuml;rkiye. Patients with a history of bariatric surgery, those who started orlistat concurrently with liraglutide, and one patient who developed pancreatitis on the 15th day of treatment were excluded from the analyses of weight and laboratory changes. Results : At least one side effect was observed in 48% of the patients, with nausea and vomiting being the most common. The most frequent reason for discontinuing treatment was the cost of the medication (42.6%). The median duration of liraglutide use was 4 months (IQR; 3-6), and the median dose was 2.4 mg (IQR; 1.8-3). Among the entire cohort, 76.4% and 40.9% of patients achieved a 5% and 10% weight loss target, respectively. Significant reductions were observed in metabolic parameters during the treatment. The treatment duration was identified as an independent predictor for achieving 5% and 10% weight loss targets (B = 0.315, p < 0.001) and 10% weight loss (B = 0.216, p < 0.001). Conclusions : Liraglutide effectively results in clinically significant weight loss, achieves expected weight loss targets, and improves metabolic parameters in real-world clinical practice. Therefore, liraglutide is still a reasonable GLP-1 analogue in the obesity treatment. However, it may be associated with various side effects, necessitating close monitoring by clinicians.
Keywords: GLP-1 analogue; Liraglutide; Obesity; Overweight